2022
DOI: 10.3390/ani12020164
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supplementation of Saccharomyces cerevisiae boulardii during Late-Gestation through Lactation Differentially Modulated Immune Status and Stress Responsiveness of the Progeny to Farrowing and Weaning Stressors

Abstract: The study aimed to investigate and characterize the maternal effects of feeding Saccharomyces cerevisiae var. boularddii (Scb) to sows from late-gestation through lactation on progeny cortisol, immune status, and stress responsiveness from birth to 14 days post-weaning. Eighty-four piglets were born to sows fed control (CON) or probiotic (PRO) boluses twice daily for 59 days. Blood samples were obtained at birth and 24 h later to assess prenatal effects; 7, 14, and 21 day-of-age to assess potential development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
0
0
1
Order By: Relevance
“…We previously reported that at birth, pigs born to sows fed probiotics had lower cortisol but higher percentages of neutrophils and lower lymphocytes than those born to control sows. However, there were no differences in either cortisol or leukocyte populations 24-h later [42]. Here, we found limited differences during the 21-day lactation period on innate and adaptive immune measures, except NK cytotoxicity being enhanced at 14 days old among those born to PROtreated sows, but at 21 days old, mitogen-induced T cell proliferation index was less than those born to CON sows.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We previously reported that at birth, pigs born to sows fed probiotics had lower cortisol but higher percentages of neutrophils and lower lymphocytes than those born to control sows. However, there were no differences in either cortisol or leukocyte populations 24-h later [42]. Here, we found limited differences during the 21-day lactation period on innate and adaptive immune measures, except NK cytotoxicity being enhanced at 14 days old among those born to PROtreated sows, but at 21 days old, mitogen-induced T cell proliferation index was less than those born to CON sows.…”
Section: Discussioncontrasting
confidence: 57%
“…Despite limited effects on the sow's immune status, there were in utero effects [42] and carry-over effects on the progeny during lactation and up to 35 days old. We previously reported that at birth, pigs born to sows fed probiotics had lower cortisol but higher percentages of neutrophils and lower lymphocytes than those born to control sows.…”
Section: Discussionmentioning
confidence: 99%
“…Boulardi (ScVB) CNCM I-1079 mejoró el rendimiento de los lechones durante la lactancia. Salak-Johnson y col. [24] refieren que, los probióticos pueden mejorar la respuesta inmunitaria innata y adaptativa de las crías de las madres tratadas con probióticos, reduciendo la capacidad de respuesta al estrés de estos lechones ante múltiples factores estresantes; así pues, Shen y col. [26] expresan que, la adición del SCFP en las dietas de las cerdas en gestación y lactancia tienen el potencial de mejorar la GdP de la camada durante la lactancia, asociado a la reducción del nitrógeno en urea plasmática, conllevando al mejoramiento de salud madre y como consecuencia la tendencia a mejorar la GdP de la cría; esto último, por la mejora de la capacidad antioxidante de los mismos [30].…”
Section: Indicadores De Parámetros Zootécnicos De Las Cerdas Durante ...unclassified
“…También SalakJohnson et al (2022) utilizaron una estrategia alimenticia similar a la de Le Floc´h et al (2022), pero midieron el nivel de cortisol de la progenie, el estado inmunológico y la capacidad de respuesta al estrés desde el nacimiento hasta los 14 días posteriores al destete. Lo que observaron fue que los cerdos nacidos de cerdas que consumieron levaduras en sus dietas tuvieron una menor secreción de cortisol y parámetros inmunológicos mejorados al nacer y 24 horas después, lo que indica menos estrés.…”
Section: Usos En Dietas Para Lechones Lactantes Y Cerdas Gestantes Y ...unclassified